Analysis of a multi-component system with failure dependency, N-policy and vacations - Gang He; Wenqing Wu; Yuanyuan Zhang (Operations Research Perspectives, 2018)
This paper studies a repairable k-out-of-n:G system with failure dependencies, N-policy and repairman's multiple vacations. Whenever there are no broken components, the repairman leaves for a vacation which obeys a phase type distribution. Upon returning from his/her vacation, he/she takes another vacation if broken components waiting less than N. This pattern continues until at least N broken components are waiting. By using the Markov process theory, the matrix analytical method and the probabilistic properties of the phase type distribution, the availability and the rate of occurrence of failures of the system are derived in transient and stationary regimes. Further, numerical examples discuss the behavior of the system reliability measures.
Keywords: 330; k-out-of-n:G system; Redundant dependency; Reliability measure; Matrix analytical method; Phase type